Információ visszakeresésekor szöveg típusú állományoknál használt indexelési technikák - Princz, Mária; Krausz, Fanni (International Journal of Engineering and Management Sciences, 2017)
Information retrieval from a typically not structured text became greatly important already more than two decades with the appearance of the Internet. Various methods are available for prosperous information retrieval. One of them is the use of inverted files that the general when searching for specific web content. This paper provides an overview of search unstructured text documents.